P0427IGA GLOMERULONEPHRITIS WITH MASSIVE PROTEINURIA- CASE SERIES WITH CLINICAL AND PATHOHISTOLOGICAL REVIEW. (6th June 2020) - Tisljar, Miroslav; Toric, Luka; Kasumović, Dino; Crnogorac, Matija; Horvatić, Ivica; Zagorec, Nikola; Galesic Ljubanovic, Danica; Galesic, Kresimir
Abstract: Background and Aims: IgA nephropathy (IgAN) is the most common glomerulonephritis worldwide. The classic manifestation of IgAN is episodic hematuria and proteinuria. Nephrotic syndrome (NS) is not common in IgAN. It is reported to occur in 5-10% of patients with IgAN. Clinical presentation with massive proteinuria is exceptional. Method: We retrospectively analyzed patients with pathohistologically proven IgAN who initially presented with 24h proteinuria greater than 10 gr. Here we presented their clinical, biochemical and pathohistological (electron microscopy-EM, was provided in all cases) characteristics with clinical outcomes. Data were taken from Renal biopsy Registry of Department of Nephrology Dubrava University hospital. Results: All together 12 patients (10 M, 2 F) average age 53 (range 25-81) years were included. This represents 3, 2% of all IgAN patients in our Renal biopsy Registry (presently there are more than 2100 patients in total, 366 with IgAN). Arterial hypertension had 10 out of 12 patients and three patients had diabetes mellitus type 2. Other significant comorbidities included lung adenocarcinoma in one patient, history of preeclampsia, mitral valve replacement surgery and liver cirrhosis, each in one patient. Average serum creatinine level at presentation was 223, 9 (90-549) µmol/L and average 24h proteinuria was 14, 6 (10, 2-32) gr. All patients had haematuria. Renal insufficiency was found in 7 patients and additionally in two patients rapidoprogressive clinical pattern was recognized. Oxford classification was applied for all patients. In all except one, mesangial hypercellularity (M1) was found, endocapillary proliferation (E1) in 4 and cellular crescents in 5 patients (C1 in 4, C2 in 1 patient). The average percentage of globally sclerosing glomeruli was 32% (10-85%) and IFTA was 33% (10-60%), respectively. On EM diffuse podocyte foot processes effacement was documented only in two patients. In patients with diabetes mellitus there were not signs of diabetic nephropathy (i.e. thickened GBM on EM). Two patients who presented with purpuric rash and arthritis were considered to have IgA vasculitis (Henoch Schoenlein purpura). Considering treatment, glucocorticosteroids and RAAS blockators (apart from those who were dialysis dependent) were introduced. Five patients were also treated with cyclophosphamide. Average time of follow-up was 53 months (2-156). Regarding clinical outcomes, 4 patients achieved remission (2 partial and 2 complete). One of those experienced clinical relaps and underwent kidney rebiosy. In one patient stationary course and in another one progression of renal insufficiency were noted. Both patients diagnosed as IgA vasculitis were dialysis depended at presentation and during follow-up period unfortunately died. Two more patients died latter on as a consequence of a non-renal disorders. One more patient who developed ESRD was transplanted but afterwards he rejected the graft. One patient was lost from follow-up. Conclusion: Proteinuria is well known independent progression risk factor in IgAN. In presented study we showed that almost one third of IgAN patients who manifested with massive proteinuria ended up in ESRD in relatively short follow-up period.